Stock Investment Decision Making Analysis with Price Earning Ratio (PER) and Capital Asset Pricing Model (CAPM) Approaches - Rizma Nazriah Hasibuan; Iskandar Muda; Rina br Bukit (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The occurrence of the Covid-19 pandemic that hit the whole world including Indonesia in early 2020 resulted in a decline in various sectors, including the stock market where many people were hesitant to invest in stocks. Various industries in Indonesia have been affected by Covid-19 where since early March 2020 there has been a decline in the LQ45 Index because many investors have sold their shares. This study aims to analyze the use of the Price Earning Ratio (PER) and Capital Asset Pricing Model (CAPM) approaches as the basis for making stock investment decisions in companies in the LQ45 Index and compare the accuracy of the Price Earning Ratio (PER) and Capital Asset Pricing Model (CAPM) approaches. This research was conducted on LQ45 Index stocks in the period February 2019 – January 2021. This study has a population of 54 stocks and a sample of 9 stocks. The sampling technique used purposive sampling technique. The results of this study indicate that with the Price Earning Ratio (PER) approach, 2 stocks are in an overvalued condition and 7 stocks are in an undervalued condition overvalued condition and 6 efficient shares or company shares that are in undervalued condition. Based on the use of the Mean Absolute Deviation (MAD) method, the results show that the MAD CAPM value is smaller than the MAD PER value (0.011 < 0, 077) which means that the CAPM method is more accurate than the Price Earning Ratio (PER) approach as the basis for making stock investment decisions. Thus, the CAPM method can be used by investors as a basis for making investment decisions to get maximum returns and minimize risk during the Covid-19 pandemic.